Pengembangan Game Edukasi Mobile Sebagai Media Pendukung Peningkatan Kecerdasan Musikal Anak di Sekolah Menengah Pertama - Alesandro Obigael Pasaribu; Ida Bagus Nyoman Pascima; Made Susi Lissia Andayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study was motivated by the suboptimal implementation of music education, particularly music notation material, in junior high schools, which has resulted in students’ low musical intelligence and the limited use of interactive technology-based learning media. This study aims to develop a mobile educational game as a learning medium to help students understand music notation and support the improvement of their musical intelligence. The method used in this study was Research and Development (R&D) with the Game Development Life Cycle (GDLC) development model, which consists of the stages of Initiation, Pre-Production, Production, Testing, Beta, and Release. The result of this study is a mobile educational game called NOMU, which has undergone validation and testing processes. The content expert validation showed a validity score of 100% with the criterion of “Highly Valid, or usable without revision,” while the media expert validation also obtained a validity score of 100% with the criterion of “Highly Valid, or usable without revision” after the refinement stage. In addition, the results of the user response test indicated a “Very Positive” qualification with a “Very Good” criterion. These results indicate that the developed mobile educational game is feasible to be used as a supporting medium for music learning and has the potential to support the improvement of students’ musical intelligence in junior high schools. The implications of this study suggest that mobile educational games can serve as innovative learning media that support the development of students’ musical intelligence and encourage the integration of digital technology in music education at the junior high school level.